CHARACTERISTICS OF IMMUNE STATUS IN NEPHROTIC SYNDROME IN ADOLESCENT CHILDREN WITH IMMUNODIATESIS (International Journal of Scientific Pediatrics, 2022)
In order to study the immune status in nephrotic syndrome in adolescent children with immunodiathesis, 120 children aged 7 to 11 years were examined. Of these: group 1 - 35 - NS (nephrotic form of CGN); 2-group -35 - NS with LD; 3- group - 25 - LD. Control group: 25 practically healthy children of the same age. It has been established that in the hormone-dependent form of nephrotic syndrome, adolescent children with immunodiathesis are characterized by pronounced clinical and laboratory symptoms, manifested by "chalky" pallor (74.2%), anasarca (9.0%), hepatosplenomegaly (57.1%), Itsenko -cushing syndrome (11.4%), severe anemia (74.2%), increased lymphocytosis (77.0%), gamma globulin (1.02 times), decreased albumin (1.3 times) and cortisol (1 ,2 times). In such patients, the immune status is characterized by impaired function of the cellular link of immunity, IL-2 production, an increase in the content of ABL-kidneys, ABL-lungs, which confirm the inclusion of adequate immunocorrective drugs in the complex treatment.
Keywords: nephrotic syndrome, immunodiathesis, teenager, immunity